Stres dan depresi berkaitan dengan emotional eating dan mindful eating pada mahasiswa saat pandemi Covid-19 - Adhila Fayasari; Putri Winda Lestari (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
Covid-19, which has spread rapidly around the world, has resulted in changes in people's life activities because the government carried out large-scale restrictions to stop the spread of the virus. The increase in eating behavior results from changes in mental health during the Covid-19 pandemic, especially in students. This study aims to analyze the relationship between stress, depression, and anxiety with emotional eating and mindful eating in college students during the Covid19 pandemic. Many students experience emotional eating and are very emotional eaters. This research was conducted in September-October 2020 on 303 student subjects using the accidental sampling technique. Research data were obtained through questionnaires distributed online. The questionnaire consisted of characteristic data, changes in body weight and eating behavior, a modified DASS-21 questionnaire to measure stress, depression, and anxiety, EEQ (Emotional eating Questionnaire), and MEQ (Mindful eating Questionnaire). The data were processed univariately in frequency and percentage and bivariate analysis with an Ordinal Spearman Correlation with an error rate of 5%. In college students, stress, depression, and anxiety are relatively high, especially at the severe stage. Stress and depression were significantly related to mindful eating (p<0,05) but not to anxiety (p>0,05). The more stressed and depressed students tend to experience non-mindful eating.